Time for things labor, leisure, and the rise of mass consumption - Rosenberg, Stephen D., 1966- (Harvard University Press, 2021)
"Time for Things seeks an answer to the question of why, in mature industrial capitalist societies, increasing productivity has tended to get used to increase output and consumption as opposed to reducing the burden of work. Put simply, why do we live in a world so full of goods, many of which have questionable or marginal value, and (by comparison) so lacking in free time?"--